1, 2-Insertion reactions of alkynes into Ge–C bonds of arylbromogermylene. Issue 21 (16th May 2020) - Sugahara, Tomohiro; Espinosa Ferao, Arturo; Rey Planells, Alicia; Guo, Jing-Dong; Aoyama, Shin; Igawa, Kazunobu; Tomooka, Katsuhiko; Sasamori, Takahiro; Hashizume, Daisuke; Nagase, Shigeru; Tokitoh, Norihiro
Abstract : 1, 2-Insertion reactions of alkynes into the Ge–C bonds in dibromodigermenes afford stable crystalline bromovinylgermylenes. Abstract : 1, 2-Insertion reactions of alkynes into the Ge–C bonds in dibromodigermenes afford stable crystalline bromovinylgermylenes. In contrast to previously reported Lewis-base-supported vinylgermylenes, the bromovinylgermylene obtained from reaction of the bromogermylene with 3-hexyne via such an 1, 2-insertion is a donor-free monomer. A feasible reaction mechanism, proposed on the basis of the observed experimental results in combination with theoretical calculations, suggests that the [1+2]-cycloadduct and the insertion product are the kinetic and thermodynamic product, respectively.